Putative alternative polyadenylation (APA) events in the early interaction of Salmonella enterica Typhimurium and human host cells - Fabian Afonso-Grunz (Genomics Data, 2015)
The immune response of epithelial cells upon infection is mediated by changing activity levels of a variety of proteins along with changes in mRNA, and also ncRNA abundance. Alternative polyadenylation (APA) represents a mechanism that diversifies gene expression similar to alternative splicing. T-cell activation, neuronal activity, development and several human diseases including viral infections involve APA, but at present it remains unclear if this mechanism is also implicated in the response to bacterial infections. Our recently published study of interacting Salmonella enterica Typhimurium and human host cells includes genome-wide expression profiles of human epithelial cells prior and subsequent to infection with the invasive pathogen. The generated dataset (GEO accession number: GSE61730) covers several points of time post infection, and one of these interaction stages was additionally profiled with MACE-based dual 3'Seq, which allows for identification of polyadenylation (PA) sites. The present study features the polyadenylation landscape in early interacting cells based on this data, and provides a comparison of the identified PA sites with those of a corresponding 3P-Seq dataset of non-interacting cells. Differential PA site usage of FTL, PRDX1 and VAPA results in transcription of mRNA isoforms with distinct sets of miRNA and protein binding sites that influence processing, localization, stability, and translation of the respective mRNA. APA of these candidate genes consequently harbors the potential to modulate the host cell response to bacterial infection.